Communs (im)matériels : enjeux épistémologiques, institutionnels et politiques - Arnaud Buchs; Catherine Baron; Géraldine Froger; Adrien Peneranda (Développement Durable et Territoires)
The aim of the “(in)tangible commons” special section is to refine the understanding of the intangible dimension of tangible commons and/or the tangible dimension of intangible commons, or even to show that this dichotomy is illusory. The research objects (urban area, water, land, cooperatives, seeds, summer pastures) are analyzed thanks to various theoretical and conceptual corpora reflecting the diversity of the disciplines mobilized (economics, geography, planning, law, management, anthropology and political science). We have chosen to grasp the combination of the tangible and intangible dimensions of the commons through three perspectives, which are not exclusive of each other. The first, the epistemological perspective, emphasizes the inherent complexity of the commons and aims at questioning the a priori according to which a specific object considered as a commons could be tangible or intangible per se. The second perspective, institutional, combines the tangible and intangible dimensions of the commons through the issues of rules shaping, particularly those related to ownership, possession and access, but also through the linked coordination issues. The third perspective deals with the links between the tangible and intangible dimensions of the commons through the political issues at stake, regarding the commons as political projects. These three perspectives structure the articulation of articles within the special section.